Multiple Biological Activities of Rhododendron przewalskii Maxim. Extracts and UPLC-ESI-Q-TOF/MS Characterization of Their Phytochemical Composition - Dai, Lixia; He, Jian; Miao, Xiaolou; Guo, Xiao; Shang, Xiaofei; Wang, Weiwei; Li, Bing; Wang, Yu; Pan, Hu; Zhang, Jiyu (Frontiers in Pharmacology, 2021)
Backgroud: Rhododendron przewalskii Maxim. is an evergreen shrub that is used as a traditional medicine in China. However, the modern pharmacology and the chemical components of this plant has not been studied. In this paper, we aimed to investigate the antifungal, anti-inflammatory and antioxidant activities and underlying mechanism of its aqueous and ethanol extracts, and analyze their chemical composition and active compounds of R. przewalskii. Methods: The antifungal activity was determined in vitro, and anti-inflammatory and antioxidant activities and underlying mechanism of its aqueous and ethanol extracts were evaluated in vitro and in RAW 264.7 cells. The chemical composition were analyzed using UPLC-ESI-Q-TOF/MS, and the contents of six compounds were determined via HPLC. Results: Both extracts of R. przewalskii showed promising anti-inflammatory activity in vitro; decreased the production of four inflammatory cytokines, namely, NO, IL-1β, IL-6 and TNF-ɑ, in RAW 264.7 cells induced by LPS; and exhibited weak cytotoxicity. The extracts significantly scavenged DPPH radicals, superoxide radicals and hydroxyl radicals to exert antioxidant effects in vitro. The two extracts also exhibited cellular antioxidant activity by increasing SOD and CAT activities and decreasing MDA content in RAW 264.7 cells induced by LPS. However, the antifungal activity of the two extracts was weak. Nine flavonoids were identified by UPLC-ESI-Q-TOF/MS. Of these, six compounds were analyzed quantitatively, including avicularin, quercetin, azaleatin, astragalin and kaempferol, and five compounds (myricetin 3-O-galactoside, paeoniflorin, astragalin, azaleatin and kaempferol) were found in this species for the first time. These compounds demonstrated antioxidant activities that were similar to those of the R. przewalskii extracts and were thought to be the active compounds in the extracts. Conclusion: R. przewalskii extracts presented promising anti-inflammatory and antioxidant activities. The extracts contained amounts of valuable flavonoids (8.98 mg/g fresh material) that were likely the active compounds in the extract and also exhibited potential antioxidant activity. These results highlight the potential of R. przewalskii as a source of natural antioxidant and anti-inflammatory agents for the pharmaceutical industry.